2021
DOI: 10.1177/1553350621990480
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Motor Imagery Training Protocols to Surgical Education: A Systematic Review and Meta-Analysis

Abstract: Objective. Motor imagery (MI) is widely used to improve technical skills in sports and has been proven to be effective in neurorehabilitation and surgical education. This review aims to identify the key characteristics of MI protocols for implementation into surgical curricula. Design. This study is a systematic review and meta-analysis. PubMed, MEDLINE, Embase and PsycINFO databases were systematically searched. The primary outcome was the impact of MI training on measured outcomes, and secondary outcomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 81 publications
0
7
0
1
Order By: Relevance
“…According to authors, cognitive training should be more adapted for intermediate to advanced surgeons to strengthen already acquired and memorized techniques (in particular, those related to spatial abilities) [55]. Otherwise, a systematic review of the literature performing a real benchmarking including wide range of studies in several MI fields suggested that a successful MI training programs could be delivered in parallel to existing surgical training, in a flexible format allowing surgeons to undertake several MI sessions in a self-directed manner [56].…”
Section: Resultsmentioning
confidence: 99%
“…According to authors, cognitive training should be more adapted for intermediate to advanced surgeons to strengthen already acquired and memorized techniques (in particular, those related to spatial abilities) [55]. Otherwise, a systematic review of the literature performing a real benchmarking including wide range of studies in several MI fields suggested that a successful MI training programs could be delivered in parallel to existing surgical training, in a flexible format allowing surgeons to undertake several MI sessions in a self-directed manner [56].…”
Section: Resultsmentioning
confidence: 99%
“…Imagery techniques can help to target pragmatic aspects of learning a procedure and also prepare learners for associated psychologic and situational stressors 4‐7 . Furthermore, the use of imagery does not rely solely on simulation devices or other physical resources, which may allow for cost saving and convenience and effective practice 13 . While simulation trainers alone have been found to improve certain procedural skills, our results indicate that imagery techniques may serve as a useful adjunct teaching method 17,30 .…”
Section: Discussionmentioning
confidence: 83%
“…12 Furthermore, the use of imagery in medical education can be implemented at little cost with promising success and utility. 13 Mental practice, relaxation, and mindfulness training had the most benefits in the surgical realm. 14 Emergency medicine residency training requires extensive experience and training.…”
Section: Introductionmentioning
confidence: 99%
“…Green et al (2019) recently reviewed the benefits of video observation in this field (see also Harris et al, 2018;Rizzolatti et al, 2021), which has shown positive effects with novice learners in a range of disciplines from arthroscopy (LeBel et al, 2018) to robot-assisted surgery (Harris et al, 2017). Goble et al (2021) and Snelgrove and Gabbott (2020) came to similar, positive conclusions in their reviews of MI in surgical training. We can only hope that history repeats itself, in that AO and MI, which a decade ago were studied and applied in isolation of each other, will be considered from an integrated perspective in future research on surgical education.…”
Section: Ao + MI Training In Motor Rehabilitationmentioning
confidence: 99%